Rekayasa Sistem Informasi Manajemen Perawatan Mesin Perkakas di Laboratorium Proses Manufaktur Jurusan Teknik Mesin Universitas Brawijaya - Rusdin, Rusdin; Santoso, Purnomo Budi; Darmadi, Djarot Bangun (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
Manufacturing Process Laboratory of Mechanical Engineering of University Brawijaya still applies the manual system in carrying out preventive maintenance. This has caused delays of action for machine maintenance and difficulties encountered by the manager or head of the laboratory with accessing to data on preventive maintenance matters to obtain the required information. Besides, there has been no encoding on the machines, components, and spare parts so that the search for information on the machines and spare parts took a long time. Therefore, a Maintenance Management Information System, which integrates Database science, Preventive maintenance, and machine tools, was created where the steps included developing the prototype. The instrument used in creating the information system was Microsoft Access 2016. Based on the testing results, the Maintenance Management Information System could generate report recaps, daily reports, warnings of available spare parts stocks, and tools and search menu. Accordingly, the information system could meaningfully assist the head of the laboratory in managing the maintenance of machines.